The legal basis for international cooperation in suppressing the crime of financing terrorism - عبيد اثير حسن; عباس سرمد عامر (Journal of Legal Sciences, 2021)
The international society feels the need to the placement of means and legal measures and procedures to fight the terrorism- financing crime , thus the UN has issued the international convention to fight the financing of terrorism for the year 1999 and a number of resolutions undertaking to control the terrorism funders in the world, specially the resolution 1373 for the year 2001 and followed by a number of states . The countries have placed legislations suited with the conditions of every state, but all of these countries agree to confront the judicial and security legislations for funding the terrorist operations، their efforts are not fulfilled unless by the support of the international cooperation for fighting these crimes